A bridge for two views: Checkland's soft systems methodology and Maturana's ontology of the observer. Issue 4 (2nd April 2020) - Paucar-Caceres, Alberto; Jerardino-Wiesenborn, Bruno
Abstract: Checkland and Maturana's work aim to understand and to improve problematic situations in organisations and in our everyday life. Maturana's phenomenological onto-epistemology (we are immersed in the praxis of living in an ontological multi-universe) seems to resonate with Soft Systems Methodology (SSM) interpretivist epistemology. We argue that this concurrence makes it possible to reflect and explore some of Maturana's ideas ( structural determinism/structural coupling/organisational closure ) when they are grafted into the phases of the Checkland's SSM seven-step process. This article aims to complement SSM by proposing a framework in which some key concepts from Maturana's Ontology of the Observer (OoO) might enhance and expand the understanding of the SSM application process. An enriched and enhanced SSM process could have significant consequences in the Management Science/Operational Research (MS/OR) and Systems community practice. The framework proposed can have major social repercussions since it will incorporate the well-known influential OoO ideas into MS/OR practice.